(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Due to the interest in Alnus glutinosa as the plantation species has increasesed in Latvia during last years, a structural unit “LVM Sēklas un stādi” of State Stock Company “Latvijas Valsts Meži” (Latvia’s State Forests) offers to the local market Alnus glutinosa bare root seedlings with an advanced root system obtained from Alnus glutinosa seeds growed in planting such selected seedlings in cutovers and for land reforestation theorectically will allow the land owner to increase the value of forest and the profit from its management. Practically, this prospects should be evaluated from the perspective of forest health.Therefore, the purpose of this study were to: (1) estimate the incidence of heart colouring and stem decay in Alnus glutinosa stands in different forest types and ages, (2) identify and measure heart colouring area /heartwood hard rot stage area diameter and soft rot stage area diameter/ cavity diameter of the stumps, (3) evaluate the relationships between stand species composition (forest types) and Alnus glutinosa stands age on heart colouring/heartwood hard rot stage and soft rot stage/cavity incidence, (4) by analysing the results to work out the recommendations to improve the forest managment in forest stands where Alnus glutinosa stands from plantations are growing.